The Effect of The Policy on Channeling of Funds and The Monitoring System Significantly on The Economic Welfare of Members at The BMT Maslahah Tiris Branch - Nasrifah, Maula (Muhasabatuna : Jurnal Akuntansi Syariah, 2025)
Purpose of this Research the formulation of the problem in this study is as follows, Does the policy on channeling funds and the supervisory system affect the economic welfare of members partially and simultaneously. To find out the effect of the policy on channeling of funds and the monitoring system significantly on the economic welfare of members partially and simultaneously at the BMT Maslahah Tiris branch. The type of research used in this study is a quantitative method with a descriptive approach. The samples and respondents in this study were members of the BMT Maslahah Tiris Branch with 96 respondents. Data collection techniques using questionnaires and documentation. Data analysis techniques used validity test, reliability test, multiple linear regression test, classical assumption test, hypothesis test and simultaneous test. The data processing uses SPSS 25. The results of the analysis show that the policy on channeling funds has a significant effect on the economic welfare of members. This is proven by the T test, a significant value of 0.000 <0.05 and a t- count value of 8,985 > t-table 1.986 so that it can be concluded that H1 is accepted, which means that there is an effect of X1 on Y. And the results of the analysis for the surveillance system show that there is a significant influence to the economic well-being of members. This is proven by the T test, the significant value for the effect of X2 on Y is 0.023 <0.05 and t count 2,315 > ttable 1.986 so it can be concluded that H2 is accepted, which means there is an effect of X2 on Y. The results of the analysis show that the distribution policy funds and supervisory systems, both of which simultaneously influence the economic welfare of member.